PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI MODEL COOPERATIVE LEARNING EXPLICIT INSTRUCTION PADA MATA PELAJARAN TEKNIK JAHIT APLIKASI DI KELAS XI DESAIN PRODUK KRIYA TEKSTIL SMK NEGERI 4 PADANG - Juwita, Syahrida; Adriani, Adriani; Nelmira, Weni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
The lack of activity and the results of learning in students of SMK N 4 Padang in sewing technique learning applications caused by learning which is still centered on the teacher (Teacher Center) and the model of learning that has not varied. To increase business activity was conducted and the results of student learning on subjects of sewing Techniques application by using the learning model of Explicit Learning Instruction Cooperatif. The research is the research of class action is done in two cycles. Each cycle three times. Each cycle consists of four steps, namely planning, implementation, observation and reflection which is used as the basis to conduct the repairs on the next cycle. The instruments used are observation sheets, tests the results of the study, and a note field. The collection of data through observation sheet is aided by an observer. The data obtained were analyzed in two ways namely qualitative data were analyzed with narration and provided arguments and quantitative data. Success criteria actions for the learning activities of students is 80%. The results of the research achievement of the learning activities of students reached 86%. Success criteria actions for student learning outcomes are 80% reached 75. The research results of student learning is 86%. The student has already obtained a value of 75. Thus it can be concluded that the use of model learning Cooperatif Learning Expicit Instruction can increase student learning outcomes and activities on subjects of sewing Techniques application of student SMK N 4 field.Keywords: Learning Activities, Learning Outcomes, Learning Cooperatif Learning Of Explicit Instruction